Impacts of genomics on the health and social costs of intellectual disability. Issue 7 (24th January 2020) - Doble, Brett; Schofield, Deborah; Evans, Carey-Anne; Groza, Tudor; Mattick, John S; Field, Mike; Roscioli, Tony
Abstract : Background: This study provides an integrated assessment of the economic and social impacts of genomic sequencing for the detection of monogenic disorders resulting in intellectual disability (ID). Methods: Multiple knowledge bases were cross-referenced and analysed to compile a reference list of monogenic disorders associated with ID. Multiple literature searches were used to quantify the health and social costs for the care of people with ID. Health and social expenditures and the current cost of whole-exome sequencing and whole-genome sequencing were quantified in relation to the more common causes of ID and their impact on lifespan. Results: On average, individuals with ID incur annual costs in terms of health costs, disability support, lost income and other social costs of US172 000, accumulating to many millions of dollars over a lifetime. Conclusion: The diagnosis of monogenic disorders through genomic testing provides the opportunity to improve the diagnosis and management, and to reduce the costs of ID through informed reproductive decisions, reductions in unproductive diagnostic tests and increasingly targeted therapies.